2023
DOI: 10.2147/idr.s428720
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Drug-Resistant Tuberculosis in Children in Shenyang, China, 2017–2021

Jiao Sun,
Lichao Fan,
Yanping Zhao
et al.

Abstract: Objective Drug-resistant tuberculosis (DR-TB) in children seriously threatens TB control. Information on the epidemiology and characteristics of DR-TB in children in China is limited. We studied data in Shenyang Tenth People’s Hospital to understand the DR-TB epidemiology in children in Shenyang. Design or Methods We retrospectively analyzed drug resistance testing data of pediatric TB patients between 2017 and 2021, and included 2976 clinically-diagnosed pediatric TB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…[ 6 ] Between 2017 and 2021, the rates of DR-TB was 28.78%, and the rates of MR-TB was 12.9% in Shengyang Province, China. [ 7 ] A retrospective study on the epidemiological characteristics and characteristics of DR-TB in children with tuberculosis in Sichuan Province from 2015 to 2018 showed that the culture-confirmed tuberculosis in children accounted for 3% of all new tuberculosis cases, which was lower than the estimated proportion of tuberculosis in children in China, with the overall rate of DR-TB at 24.3% and the rate of MDR-TB at 5.4%. [ 8 ] The analysis by Zignol et al [ 9 ] found that the risk of MDR-TB was similar in children between under 5 years and 5 to 14 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Between 2017 and 2021, the rates of DR-TB was 28.78%, and the rates of MR-TB was 12.9% in Shengyang Province, China. [ 7 ] A retrospective study on the epidemiological characteristics and characteristics of DR-TB in children with tuberculosis in Sichuan Province from 2015 to 2018 showed that the culture-confirmed tuberculosis in children accounted for 3% of all new tuberculosis cases, which was lower than the estimated proportion of tuberculosis in children in China, with the overall rate of DR-TB at 24.3% and the rate of MDR-TB at 5.4%. [ 8 ] The analysis by Zignol et al [ 9 ] found that the risk of MDR-TB was similar in children between under 5 years and 5 to 14 years of age.…”
Section: Introductionmentioning
confidence: 99%